Effect of extrusion conditions and postextrusion techniques on the morphology and thermal/mechanical properties of polycaprolactone/clay nanocomposites - Ludueña, Leandro Nicolas (2013)
The effect of extrusion conditions on the performance of polycaprolactone /organo-modified clay nanocomposites was studied. It was demonstrated that the extrusion parameters have negligible effect on the molecular weight of polycaprolactone, on the morphology of the nanocomposites and on the final thermal/mechanical properties of the materials. This result was a consequence of the previous optimization of both polymer/clay compatibility and clay processing stability. Finally, the molten-polycaprolactone/clay mixtures were post-processed by different techniques submitting the mixtures to extensional flow. Clay platelets alignment was observed as a function of the extensional flow intensity which further improved the mechanical properties of the nanocomposites.